Polyphenolic Screening and the Antioxidant Activity of Grape Pomace Extracts of Romanian White and Red Grape Varieties - Cristiana Radulescu; Radu Lucian Olteanu; Claudia Lavinia Buruleanu; Mihaela Nechifor (Tudorache); Ioana Daniela Dulama; Raluca Maria Stirbescu; Ioan Alin Bucurica; Sorina Geanina Stanescu; Andreea Laura Banica (MDPI AG, 2024)
Due to its valuable organic compounds, grape pomace represents a valuable resource in the creation of value-added food products. In this study, we investigated grape pomace hydroalcoholic extracts obtained by ultrasonication from two white and two red Romanian grape varieties. The phytochemical parameters, i.e., polyphenolics, flavonoids, anthocyanins, condensed tannins content, and antioxidant activity, were determined by UV-Vis spectrometry. The statistical analysis revealed that Tămâioasă Românească and Negru de Drăgășani, respectively, and Fetească Albă and Fetească Neagră are similar to each other. Significant differences among the pomaces obtained from different grape varieties were noticed in terms of their phenolic contents. The red varieties (Fetească Neagră and Negru de Drăgășani) were richest in terms of total phenolics and total anthocyanins, respectively. The antioxidant activity of extracts obtained from grape pomace showed that Negru de Drăgășani had the higher value due to its high amounts of polyphenols, followed by Fetească Neagră, Fetească Albă, and Tămâioasă Românească. Higher levels of bioactive polyphenolic substances, i.e., catechin, myricetin, resveratrol, and vanillic acid, were found in the pomace of Negru de Drăgășani extracts using high-performance liquid chromatography. These results emphasize the potential of the Negru de Drăgășani variety to be further exploited for nutritional and functional applications.